Perfil epidemiológico e nível sérico de ácido fólico em mães de crianças portadoras de defeito do tubo neural - Pereira, Jesus Henrique Nicola (2011)
Neural tube defects (NTDs), which is a congenital malformation, in significant part on the statistics of perinatal morbidity and mortality due to their high incidence rates. The DA can be limited to the central nervous system and / or peripheral, and may also include the overlying tissues (bones, muscles and connective tissue). Folic acid (FA) is a nutrient that plays a fundamental role in the process of cell multiplication. And the remarkable importance of folic acid in preventing NTDs where published studies portray the relationship between the levels of PA and the birth of children with NTDs, whereby the higher the rate of serum folate, less frequent are the births of children with NTDs . Although he knows that the AF is directly linked to the prevention of NTDs, little has been epidemiologically demonstrated the use of it in our population (especially from the Northeast-SE Brazil). All study women received prenatal (PN), however from the second month of conception outside the period in which it is contemplated by the AF prevention, highlighting the lack of an effective family planning. Was not performed by folic acid supplementation in 56.6% of women studied and the other 43.3% who did, began after the second month of pregnancy, which had become ineffective in the prevention, the same vitamin, the DTN. Showed that only 3.3% of cases of NTD group had a gestational age was less than 37 weeks and 50% were primigravida, the same group. The women studied were aged 24.8 years on average to become pregnant. Epidemiological parameters when compared with the comparison group, were similar, since both groups used the same health service, with the characteristic of high risk. The levels of serum folate in a group of women studied, remained normal and the highest of scientific studies published so far with similar characteristics. Prevention with the use of folic acid should be intensified by the various sectors of society, the risk group studied, so to avoid the recurrence of neural tube defects, reducing the incidence and recurrence in women who are more likely to generate conceptuses with this malformation.